Mapping and expression of a regulatory nitrogen fixation gene (fixD) of Rhizobium meliloti - Weber, Gerhard (1985)
A 3.5-kb HindIII fragment from the main nif/fix (nitrogen fixation) gene cluster of Rhizobium meliloti was characterized by studying its expression in Escherichia coli minicells. A coding region for two polypeptides of 68 K and 66 K was mapped using Tn5 insertions and hybrid fusion polypeptides. DNA sequence analysis of this region revealed the presence of an open reading frame capable of coding for a polypeptide of 59.9 K mol. wt. This coding region was designated fixD. Plasmids, constitutively expressing this fixD gene from vector promoters, activated a nifHD-lacZ fusion in E. coli at a low level. Higher levels of activation were obtained following an enhanced expression of the fixD gene in plasmid pRmW541 which was achieved by inducing deletions between the vector promoter and the fixD gene. Sequencing of these deletion mutants showed that, in most cases, fusion polypeptides of the fixD gene product and the aphI (aminoglycoside-3'-phosphotransferase) gene product were sufficient for activation. In E. coli the activation is strictly dependent upon a functional glnF (ntrA) gene.